Screening soil erosion risk potential in the municipality of Subang Jaya with regards to rainfall and soil characteristics / Adnan Derahman - Derahman, Adnan (2008)
The soil erosion potential study under the jurisdiction of Subang Jaya Municipal Council covers an area of 161.8KM2. A total of 20 soil samples were collected from various slope locations within the council's area.